Implementasi Media Topeng Fantasi untuk Meningkatkan Karakter Cinta Budaya Daerah - Kusmiati Kusmiati (Jurnal Didaktika Pendidikan Dasar, 2020)
The research purpose is to describe the implementation of Fantasy Mask media for improving the character in loving the local culture, creative thinking skills, and literacy through project-based learning in writing fantasy stories in Sabilillah Islamic Junior High School Malang. The design is a classroom action research. The research subjects involved the 32 seventh graders in Sabilillah Islamic Junior High School in Malang. The research results show an increase in loving the local culture; in the first cycle, the percentage of completeness reached 87.10% and 96.77% in the second cycle. This value shows the character of loving local culture of students in good categories to excellent categories, 2) there is an increase in the students' creative thinking skills in the first cycle with the completeness of 80.64% increase to 93.54% in cycle II. The students' creative thinking skills were improved from fairly good to a very good category, and 3) there is an increase in literacy skills in the first cycle with a percentage of 83.87 increasing to 96.77% in the second cycle.